Identifying regions of disease-related variants in admixed populations with the summation partition approach. Issue 7 (October 2016) - Auerbach, Jonathan; Agne, Michael; Fan, Rachel; Lo, Adeline; Lo, Shaw-Hwa; Zheng, Tian; Wang, Pei
Abstract We propose a new method for identifying disease-related regions of single nucleotide variants in recently admixed populations. We use principal component analysis to derive both global and local ancestry information. We then use the summation partition approach to search for disease-related regions based on both rare variants and the local ancestral information of each region. We demonstrate this method using individuals with high systolic blood pressure from a sample of unrelated Mexican American subjects provided in the 19th Genetic Analysis Workshop.